The Dialectical Mandala Model of Self-cultivation - Azanlansh, Orchid-Stone Chang (Frontiers in Psychology, 2023)
This paper explores the development of a cross-cultural primary ontological model that can help self-cultivation practitioners illuminate their path and help researchers identify the complex implications, context, and progression of self-cultivation in diverse cultures, especially those associated with Buddhism, Taoism, and Confucianism. Integrating self-cultivation traditions into social science research from the perspective of subject-object dichotomy is difficult. However, the assimilation of the mutual implication of subject and object in the Avataṃsaka worldview helps resolve this issue. This paper employs the Buddhist tetralemmic dialectic (catuṣkoṭi), which goes beyond the limitations of dualistic and reductionist logic, to construct the Dialectical Mandala Model of Self-cultivation as the first of a two-step epistemological strategy. The model provides a universal framework for the multifaceted and systemic analysis of self-cultivation traditions so that future research can further develop additional culturally specific ontologies and psychological models in the second step of the strategy. As in a research map, this model could help researchers make ontological commitments, understand self-cultivation from a more comprehensive perspective, and determine whether they have overlooked any research domain.